The Legacy of J. William Fulbright : Policy, Power, and Ideology - Snyder, David J., 1967-; Scott-Smith, Giles, 1968-; Brogi, Alessandro, 1963- (Book collections on Project MUSE., 2019)
"J. William Fulbright (1905-1995) represented Arkansas as a US Senator for almost 30 years and was the longest serving chairman in the history of the Senate Foreign Relations Committee. A Southern Democrat and a liberal internationalist who supported the creation of the United Nations, he battled against the Republican forces of Joseph McCarthy and John Foster Dulles. When President Johnson intensified American involvement in Vietnam, Fulbright became outspoken in his staunch opposition. Throughout his career, Fulbright also advocated for an international order based on interpersonal connection and mutual understanding, and he saw programs of educational and cultural exchange as necessary for the creation of such a world. Thus, his efforts to establish an international exchange program eventually resulted in the creation of a fellowship program that bears his name, the Fulbright Program. In The Legacy of J. William Fulbright: Policy, Power, and Ideology, editors Alessandro Brogi, Giles Scott-Smith, and David J. Snyder bring together fourteen essays to offer a critical analysis of both Fulbright the politician and Fulbright the program. By framing their investigation within a wider reevaluation of liberal internationalism, the manuscript addresses ongoing debates on ideology, consistency, and imperialism within US foreign policy throughout the twentieth century. The volume's multi-dimensional focus covers Fulbright's difficulties in maintaining a national and a global voice on foreign relations while wrestling with the political controversies of the US South during the civil rights movement, his involvement in domestic political controversies, and the relevance of his exchange program historically and in present day"--